2022
DOI: 10.1038/s41598-022-19928-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection in a growing colony biases results of mutation accumulation experiments

Abstract: Mutations provide the raw material for natural selection to act. Therefore, understanding the variety and relative frequency of different type of mutations is critical to understanding the nature of genetic diversity in a population. Mutation accumulation (MA) experiments have been used in this context to estimate parameters defining mutation rates, distribution of fitness effects (DFE), and spectrum of mutations. MA experiments can be performed with different effective population sizes. In MA experiments with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…In particular, our quantitative expression for the fitness cost of aneuploid individuals (see Fig. 3 and and Eq.4) could be use to account for fitness effects in MA setups and correct the estimate of the missegregation rate [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, our quantitative expression for the fitness cost of aneuploid individuals (see Fig. 3 and and Eq.4) could be use to account for fitness effects in MA setups and correct the estimate of the missegregation rate [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our modeling framework could be deployed to design and investigate Mutation Accumulation (MA) experiments aimed at measuring the mis-segragation rate. In particular, our quantitative expression for the fitness cost of aneuploid individuals (see Fig.3 and and Eq.4) could be use to account for fitness effects in MA setups and correct the estimate of the missegregation rate [64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…This finding echoes previous studies reporting changes in mutation rates in mutation-accumulation experiments (Perfeito et al 2014; Singh et al 2017). Indeed, recent studies have concluded that positive selection is possible in mutation-accumulation experiments despite the extreme bottlenecks imposed on the population (Mahilkar et al 2022; Wahl and Agashe 2022). Here, the over-representation of mutations in the genetic elements that confer the strongest hypermutator phenotypes indicates adaptive evolution through positive selection to reduce the mutation rate.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on how a researcher picks and spreads their colonies, edge effects may skew cell division estimates, as some parts of a colony experience more divisions than others [26]. Though single-cell bottlenecks are expected to overwhelm any but the most stringent selection (lethality), the harmonic mean effective population size is closer to 14 than 1 [25,16]; Several authors propose selection is a significant factor in a generic MA experiment, either throughout or in at least the first two weeks [2]. Colony choice instigated by researchers during serial bottlenecking is also at risk of researcher bias, in that humans tend to pick the colonies they can see, rather than just any colony.…”
Section: Introductionmentioning
confidence: 99%